2016
DOI: 10.4103/2231-4040.184593
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating bionanoparticle infused fungal metabolites as a novel antimicrobial agent

Abstract: Therapeutic properties of fungal metabolites and silver nanoparticles have been well documented. While fungal metabolites have been used for centuries as medicinal drugs, potential of biogenic silver nanoparticles has recently received attention. We have evaluated the antimicrobial potential of Aspergillus terreus crude extract, silver nanoparticles and an amalgamation of both against four pathogenic bacterial strains. Antimicrobial activity of the following was evaluated – A. terreus extract, biogenic silver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…These findings suggested that the cell death had occurred which may be due to necrosis or apoptosis. The cytotoxic effects probably occurred due to the interference of Ag NPs with the proper functioning of the protein leading to the change in the cellular chemistry also suggested by Rogers et al (2008) and Rajpal et al (2016a,b). Several researchers have suggested that once the Ag NPs penetrates inside the cells, they may cause partial unfolding and cause aggregation of the proteins and also interact with thiol rich enzymes (Morones et al, 2005; Zolghadri et al, 2009).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These findings suggested that the cell death had occurred which may be due to necrosis or apoptosis. The cytotoxic effects probably occurred due to the interference of Ag NPs with the proper functioning of the protein leading to the change in the cellular chemistry also suggested by Rogers et al (2008) and Rajpal et al (2016a,b). Several researchers have suggested that once the Ag NPs penetrates inside the cells, they may cause partial unfolding and cause aggregation of the proteins and also interact with thiol rich enzymes (Morones et al, 2005; Zolghadri et al, 2009).…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, it is desirable to develop biocompatible and profitable methods that can either passively or actively target cancerous cells, thereby reducing adverse side effects while improving therapeutic efficacy. Biosynthesized nanoparticles have paved the way and attracted researchers across the world due to their specific properties and wide applications in biomedical sciences (Shin et al, 2009; Zhou et al, 2011; Aziz et al, 2015, 2016; Rajpal et al, 2016a; Khan et al, 2017). Silver nanoparticles (Ag NPs) have potential to treat a variety of diseases, such as retinal neovascularisation (Ong et al, 2013) and have been investigated among the emerging nanoproducts and novel cancer therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Method validation: The developed method underwent validation to ensure its suitability analyzing selpercatinib and its impurities. Parameters such as specificity, accuracy, precision, linearity, sensitivity, ruggedness and reproducibility were evaluated according ICH guidelines [13][14][15] and literature [16][17][18][19][20][21][22][23].…”
Section: Methodsmentioning
confidence: 99%
“…The combination of green synthesis and pseudo-capacitors holds promise for advancing energy storage technologies with a focus on sustainability [6,7]. Ongoing research is likely to uncover new green synthesis methods, novel materials and optimized device designs for improved performance and widespread practical applications [8]. Onion seeds, derived from the onion plant (Allium cepa), are small, dry seeds that serve as the reproductive units of the onion flower [9].…”
Section: Introductionmentioning
confidence: 99%